Controllers’ Role and Controller’s Role in Organizations: Perception of Graduates of Accounting Sciences - Mondini, Vanessa Edy Dagnoni; Tambosi, Silvana Silva Vieira; Lavarda, Carlos Eduardo Facin (Revista de Negócios, 2018)
The demand for professionals prepared to assume strategic positions such as that of controller makes it fundamental that concepts and attributions proper to the function are known by future professionals who will exercise them. In this way, this study aims to verify the students’ perception in Accounting Sciences about the responsibilities of Controllership and the role of the Controller in organizations. For this, the definitions and attributions pertinent to the area of control were defined as Borineli (2006). The data, collected from 233 undergraduate students of accounting sciences from 10 universities in Santa Catarina, were evaluated through descriptive linear regression analysis and statistical techniques such as mean analysis, Kruskal-Wallis test of independent samples and non-parametric test sample. The results indicated that there is agreement that the control functions are related to operational activities. However, higher averages were found in the issues that related control to more strategic management activities. This indicates that there is already a perception on the part of undergraduates in the accounting sciences that the controllership has assumed an increasingly strategic position in the organizations.Â